The economic role of Russia's subsistence agriculture in the transition process - Wehrheim, Peter; Wobst, Peter (Wiley, 2005)
In this article, we analyze the role of subsistence‐oriented agriculture in Russia in the 1990s. We start out by discussing the diverging economic effects of the growth of subsistence agriculture in Russia since the transition process started. The quantitative analysis of this sector's role is carried out by means of an applied computable general equilibrium (CGE) model applying a 1994 social accounting matrix (SAM) as base year data. The novelty of the article is to disaggregate primary agricultural production not by products but by farm types, which enables us to distinguish their institutional and economic characteristics. The model also explicitly differentiates between marketed and subsistence consumption or formal and informal marketing activities of agricultural producers. We simulate two ex post and two ex ante experiments. The results of the first backward‐looking experiment highlight that Russia's subsistence agriculture was an important buffer against further agricultural output declines during transition and, hence, against food insecurity. A simulation, which looks into the effects of a devaluation of the Russian ruble, shows that the financial crisis should have increased the relative competitiveness particularly of large‐scale crop farms versus small‐scale farms. Two forward‐looking experiments indicate that efficiency enhancing institutional change would benefit both large‐scale and small‐scale farms. However, within small‐scale agriculture, a shift from subsistence to commercial agriculture would take place.